2000
DOI: 10.1016/s1074-7613(00)00078-9
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Th1 Differentiation by IL-6 Is Mediated by SOCS1

Abstract: Interleukin 6 (IL-6) is a cytokine produced by immune and nonimmune cells and exhibits functional pleiotropy and redundancy. IL-6 plays an important role in the differentiation of several cell types. Here, we describe a novel function of IL-6: the negative regulation of CD4+ Th1 cell differentiation. While IL-6-directed CD4+ Th2 differentiation is mediated by IL-4, inhibition of Th1 differentiation by IL-6 is independent of IL-4. IL-6 upregulates suppressor of cytokine signaling 1 (SOCS1) expression in activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
281
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 357 publications
(298 citation statements)
references
References 55 publications
14
281
0
1
Order By: Relevance
“…In this regard, IL-6 was found to inhibit IFN-g receptor-STAT1 signaling-dependent T H 1 differentiation directly through the unregulation of suppressor of cytokine signaling 1 (45). MDSC-induced loss of STAT1 activation in response to IFN-a or IFN-g has been reported in a murine adenocarcinoma model (46), further supporting a link between IFN-g signaling and MDSC-derived IL-6.…”
Section: Discussionmentioning
confidence: 85%
“…In this regard, IL-6 was found to inhibit IFN-g receptor-STAT1 signaling-dependent T H 1 differentiation directly through the unregulation of suppressor of cytokine signaling 1 (45). MDSC-induced loss of STAT1 activation in response to IFN-a or IFN-g has been reported in a murine adenocarcinoma model (46), further supporting a link between IFN-g signaling and MDSC-derived IL-6.…”
Section: Discussionmentioning
confidence: 85%
“…IL-6 has been previously implicated in promoting Th2 differentiation through both IL-4-dependent and -independent mechanisms (33,34). IL-6 can also promote T cell survival (35,36), raising the possibility that limiting amounts of IL-6 might contribute to the arrested phenotype.…”
Section: Resultsmentioning
confidence: 99%
“…Generally considered as a Th2 cytokine, IL-10 is able to affect Th1/Th2 balance, promote Th2 development, and inhibit Th1 differentiation. It has been shown that inhibition of Th1 differentiation by IL-6 is mediated by SOCS1 (40). It is possible that SOCS1 also plays an important role in regulating Th1/Th2 immune derivation by IL-10, directly inhibiting IFN-␥ signals and Th1 differentiation.…”
Section: Discussionmentioning
confidence: 99%